Ivacaftor Reduces Inflammatory Mediators in Upper Airway Lining Fluid From Cystic Fibrosis Patients With a G551D Mutation: Serial Non-Invasive Home-Based Collection of Upper Airway Lining Fluid - Mainz, Jochen G.; Arnold, Christin; Wittstock, Kara; Hipler, Uta-Christina; Lehmann, Thomas; Zagoya, Carlos; Duckstein, Franziska; Ellemunter, Helmut; Hentschel, Julia (Frontiers in Immunology, 2021)
In cystic fibrosis (CF) therapy, the recent approval of CF-transmembrane conductance regulator (CFTR) channel modulators is considered to be the major breakthrough. However, the current first-line approach based mainly on pulmonary function to measure effects of the novel therapy, tested by forced expiratory volumes in one second (FEV1), provides restricted sensitivity to detect early structural damages. Accordingly, there is a need for new sensitive surrogate parameters. Most interestingly, these should quantify inflammation that precedes a decline of pulmonary function. We present a novel method assessing inflammatory markers in the upper airways’ epithelial lining fluid (ELF) obtained by nasal lavage (NL). In contrast to broncho-alveolar lavage, ELF sampling by NL is an attractive method due to its limited invasiveness which allows repeated analyses, even performed in a home-based setting. In a longitudinal cohort study (ClinicalTrials.gov, Identifier: NCT02311140), we assessed changes of inflammatory mediators in 259 serially obtained nasal lavages taken up to every second day before and during therapy with ivacaftor from ten CF patients carrying a G551D mutation. Patients were trained to sample NL-fluid at home, to immediately freeze and transfer chilled secretions to centers. Neutrophil Elastase, Interleukins IL-1β, IL-6 and IL-8 in NL were quantified. During 8-12 weeks of ivacaftor-treatment, median values of IL-1β and IL-6 significantly declined 2.29-fold (2.97→1.30 pg/mL), and 1.13-fold (6.48→5.72 pg/mL), respectively. In parallel, sweat tests and pulmonary function improved considerably. This is the first study assessing changes of airway inflammation on a day-to-day basis in CF patients receiving a newly administered CFTR-modulator therapy. It proves a decline of airway inflammation during ivacaftor-therapy.